OPTIMALISASI PERAN KADER KESEHATAN DALAM PENCEGAHAN TB PARU MELALUI EDUKASI, DETEKSI DINI, DAN PENDAMPINGAN PASIEN - Yolanda anastasia Sihombing; Liang Kevin Arsastha; Emmanuela Ranita Molenaar; Selly Ruth Defianna Sidabalok (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aimed to strengthen the capacity of health cadres in TB prevention through education, early detection training, and patient assistance. Health cadres play a strategic role due to their closeness to the community, interpersonal communication skills, and function as a bridge between health workers and the community. Their involvement is essential to improve public knowledge, facilitate early detection of symptoms, assist patients in adhering to treatment, and reduce the stigma still attached to TB patients. By empowering cadres, TB control efforts can be more effective, sustainable, and community-based. The program involved 20 health cadres and applied several methods, including interactive lectures, discussions, simulations, role play, and pre–post tests to assess improvements in knowledge and skills. The results knowledge, screening ability, and skills in patient assistan ce. Cadres also demonstrated a strong commitment to actively serve as partners of health professionals. This program proves that empow ering health cadres through participatory approac hes is effective in supporting pulmona TB prevention & control at the community level.